Dynamic strain aging in Fe-Mn-Al-C lightweight steel. (2nd July 2020) - Shin, Jong-Ho; Jang, Jae Hoon; Kim, Sung-Dae; Park, Seong-Jun; Lee, Jehyun
ABSTRACT: Serrated flow in high-Mn lightweight steel was examined in the temperature range of 25–425°C with strain rates of 3.33 × 10 −4, 3.33 × 10 −3 and 3.33 × 10 −2 s −1 . Transmission electron microscopy (TEM) analysis showed a bowing dislocation line caused by an interaction between dislocations and the solute in the solid-solution. The activation energy of carbon diffusion for serration generation in this steel was about 40% lower than that of other austenite steels. A first-principles calculation showed that the activation energy of carbon diffusion in high-Mn lightweight steel was 40% lower than that in the conventional austenitic steels.